2017
DOI: 10.1186/s12933-016-0484-4
|View full text |Cite
|
Sign up to set email alerts
|

Exercise mediated protection of diabetic heart through modulation of microRNA mediated molecular pathways

Abstract: Hyperglycaemia, hypertension, dyslipidemia and insulin resistance collectively impact on the myocardium of people with diabetes, triggering molecular, structural and myocardial abnormalities. These have been suggested to aggravate oxidative stress, systemic inflammation, myocardial lipotoxicity and impaired myocardial substrate utilization. As a consequence, this leads to the development of a spectrum of cardiovascular diseases, which may include but not limited to coronary endothelial dysfunction, and left ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 227 publications
(237 reference statements)
0
33
0
2
Order By: Relevance
“…Moreover, exercising regularly has been found to be associated with major improvements in the quality of life and cardiac function (33,34). Although the precise molecular mechanism(s) of action remain unclear, physical exercise has been advocated as a non-pharmacological adjuvant to strengthen the conventional management and prevention of cardiovascular events (35). A series of clinical and experimental studies has demonstrated that an appropriate volume and intensity of exercise can ameliorate myocardial dysfunction through the improvement of maximum oxygen consumption, LVEF, LV diastolic and systolic volumes, ventilatory threshold, cardiac output and diastolic function (E/A ratio) (3538).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, exercising regularly has been found to be associated with major improvements in the quality of life and cardiac function (33,34). Although the precise molecular mechanism(s) of action remain unclear, physical exercise has been advocated as a non-pharmacological adjuvant to strengthen the conventional management and prevention of cardiovascular events (35). A series of clinical and experimental studies has demonstrated that an appropriate volume and intensity of exercise can ameliorate myocardial dysfunction through the improvement of maximum oxygen consumption, LVEF, LV diastolic and systolic volumes, ventilatory threshold, cardiac output and diastolic function (E/A ratio) (3538).…”
Section: Discussionmentioning
confidence: 99%
“…Although the precise molecular mechanism(s) of action remain unclear, physical exercise has been advocated as a non-pharmacological adjuvant to strengthen the conventional management and prevention of cardiovascular events (35). A series of clinical and experimental studies has demonstrated that an appropriate volume and intensity of exercise can ameliorate myocardial dysfunction through the improvement of maximum oxygen consumption, LVEF, LV diastolic and systolic volumes, ventilatory threshold, cardiac output and diastolic function (E/A ratio) (3538). In the present study, the patients in the CCM group received telemonitoring from primary nurses and exercise training, which might partly explain the ameliorative effects of CCM on quality of life and cardiac function.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs are small noncoding RNA molecules of approximately 22-24 nucleotides that participate in the transcriptional and posttranscriptional regulation of gene expression [69]. A variety of miRNAs have been shown to regulate hypertension, coronary heart disease, and glucose and lipid metabolism disorders [70,71]. In this study, miR-100, miR-297, and miR-758 were chosen as candidate genes after miRNA database prediction indicated that they interact with Col3a1, Agtr1a, and Col1a2, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to ART-associated DNA methylation and chromatin acetylation modifications, the role of noncoding RNAs in regulating gene expression has become a concern in IVF-ET offspring [36]. It is known that multiple microRNAs (miRNAs) are involved in the regulation of hypertension, coronary heart disease, and glycolipid metabolic disorders [37,38]. However, few studies have focused on whether ART affects the expression of miRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…Decreased plasma level of miR-21 was found in patients with diabetes in large population-based cohorts [2628]. Recently, it was found that miRNAs mediated the benefits of exercise and bariatric surgery to the heart in diabetic/prediabetic patients, and the decreased circulating miR-21 were restored after bariatric surgery or physical activity [25, 29]. Moreover, upregulation of miR-21 or downregulation of its targets could lead to diabetic cardiac dysfunction [3032].…”
Section: Introductionmentioning
confidence: 99%